2000
DOI: 10.2307/1593097
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Infectious Bronchitis Viruses Isolated from Outbreaks of Disease in Commercial Flocks in Brazil

Abstract: Fifteen isolations of infectious bronchitis (IB) virus were made from a total of 126 Brazilian poultry flocks of all ages that were examined. These flocks (14 chicken and 1 quail) were experiencing a variety of IB-like conditions including respiratory disease, digestive and kidney problems, and drops in egg production. One of the isolates was of the Massachusetts serotype. The remainder were examined by means of cross-neutralization tests in tracheal organ cultures and were shown to belong to at least four ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 19 publications
2
30
0
2
Order By: Relevance
“…The genetic relationships between Brazilian isolates and vaccine or foreign IBV strains also remain barely known. However, this study demonstrated the occurrence of high variability among IBV Brazilian isolates, as some recent investigations found about the antigenic and genetic variability of nucleotide sequences occurring among some Brazilian isolates (Di Fabio et al 2000, Abreu et al 2006a,b, Brentano et al 2006, Villarreal et al 2006a.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The genetic relationships between Brazilian isolates and vaccine or foreign IBV strains also remain barely known. However, this study demonstrated the occurrence of high variability among IBV Brazilian isolates, as some recent investigations found about the antigenic and genetic variability of nucleotide sequences occurring among some Brazilian isolates (Di Fabio et al 2000, Abreu et al 2006a,b, Brentano et al 2006, Villarreal et al 2006a.…”
Section: Resultssupporting
confidence: 59%
“…The majority of Brazilian IBV field isolates recovered up to 1989 were classified as Mass (Massachusetts) serotype (Ito 2006). However, Di Fabio et al (2000) found, among fifteen field IBV isolates, only one as belonging to the Mass serotype and the other fourteen were classified into distinct antigenic groups from ones described previously in other countries.…”
Section: Introductionmentioning
confidence: 67%
“…New variant strains may differ as much as 55% in their S1 amino acid sequence compared with vaccine strains (Kusters et al ., 1989;Gelb et al ., 1997). Many ''new'' variants have been isolated from commercial flocks (Davelaar et al ., 1984;Kusters et al ., 1989;Gelb et al ., 1991Gelb et al ., , 1997Gelb et al ., , 2001Cavanagh et al ., 1992;Gough et al ., 1992Gough et al ., , 1996Capua et al ., 1994;Moore et al ., 1998;Fabio et al ., 2000;Zeigler et al ., 2002;Schikora et al ., 2003;Meir et al ., 2004). Two genetic-based strategies have been used in the US and Israel to identify field strains; restriction fragment length polymorphism (RFLP) analysis (Kwon et al ., 1993;Meir et al ., 2004), and reverse transcription-polymerase chain reaction (RT-PCR) product cycle sequencing .…”
Section: Introductionmentioning
confidence: 99%
“…Pathotyping of the four selected Brazilian strains showed that they all caused a considerable level of ciliostasis in the trachea but at a somewhat lower level than M41 and the four Brazilian strains 50/96, 57/96, 62/96, and 64/96 of four different serotypes that were reported by Cook et al (1999) and Di Fabio et al (2000). In this last paper these strains were coded differently, being 1, 8, 13 and 15, respectively.…”
Section: Discussionmentioning
confidence: 71%
“…Experiments reported by Cook et al (1999) and Di Fabio et al (2000) showed that 14 out of 15 field isolates obtained in 1995 were of the non-Massachusetts (Mass) serotype and belonged to at least four antigenic groups that were different from the ones described in other countries. Genotyping was not performed for those strains but vaccination with a Mass vaccine (Nobilis IB MA5) at the day of hatch was able to induce heterologous cross-protection in the respiratory tract at 5 weeks post challenge, varying from 37% to 88% following challenge with strains representing the four different serotypes.…”
Section: Introductionmentioning
confidence: 91%